Coronary Artery Bypass Grafting on beating heart in Norvic Hospital - Baidya, PR; Malhotra, R; Koheli, V (Nepalese Heart Journal, 2004)
Coronary artery bypass grafting (CABG) with the use of Heart Lungs machine (extra corporeal circulation) is associated with certain risks, which may be avoided by using the Octopus stabilizer - beating heart bypass surgery (off pump). We demonstrate the early results of 44 cases of CABG on beating heart in Norvic - Escort International Hospital.